Percepção dos agentes locais na adoção da certificação de indicação geográfica: o caso dos doces de Pelotas - Almeida, Sabrina Cantarelli (2014)
The adoption of Geographical Indication (GI) certification represents, among other aspects, a way of innovation and a market advantage. Once studies on this area are recent and few in Brazil, this research had as objective to verify the historical, cultural and economic perception of the actors involved in the production chain of Pelotas sweets in relation to the adoption of Geographical Indication certification. The major promotion of Pelotas sweets is through a fair called Feira Nacional do Doce (FENADOCE), which aims at promoting the sweets culture of the region of Pelotas/RS to the country as well as abroad. The fair also plays a significant economic, cultural and historical role. The case study was carried out through a field research with primary data collection by means of search forms applied to Pelotas sweets consumers and to producer companies, that is, 3 producers that have the GI stamp, 3 associated producers without the IG and 3 producers out of the association, all of them that participated in the fair, 21st FENADOCE, between May 31st and June 2nd, 2013. The results reveal that the consumers with more knowledge about geographical identification are more inclined to pay more for a certified sweet. However, the cost plays a secondary role since the consumers are more influenced by the taste and the beauty of the sweets displayed on the shop windows of the sweets stores. In this sense, the geographical identification is seen not only as a historical and cultural review of the traditional sweets heritage, but also, as a quality assurance stamp. Therefore, with this study we can conclude that the adoption of the IG certification brought to the confectioners recognition and commercial success. The consumers started to be sure of consuming a product that maintains the characteristics of its original recipes and, of course, the unmistakable flavor of Pelotas sweets.